Eddy Current Braking Study for Brake Disc of Aluminium, Copper and Zink - Mohamad Zairi, Baharom; Priyandoko, Gigih; M.Z., Nuawi; S.M, Harris; L.M, Siow (2011)
An eddy current braking experiment was conducted to study the behaviour of three different materials to be used as brake disc which are aluminium, copper and zink. The experiment also aimed to see the effects of increasing the current induced into electromagnet which produce drag force that will slow down the motion. Results from the experiment have been recorded using optical tachometer connected to PULSE analyzer which captured the speed (RPM) and time (s). A few graph been presented in this paper to show the best material to be used as the brake disc for electromagnetic braking system using eddy current project. This preliminary result will leads to a deeper research in field of electromagnetic braking and its potential application.